Metaphor Unveiled: Exploring Translation Techniques in the Novel - Suriadi, M. Agus; Widianti, Aisah Nur; Cholifah, Cholifah (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2024)
This qualitative study employs an explanatory case study methodology to unravel metaphor translation procedures, drawing from Peter Newmark's insights and Eugene Nida's translation equivalence theory. Unveiling a captivating dance between languages, the research showcases prevalent procedures such as replacing source language images with standard ones in the target language and converting metaphors into senses. The results illuminate how these techniques offer a distinct interpretation in the target language, ensuring a nuanced conveyance of the original message. A particularly enchanting aspect is the prevalence of dynamic equivalence, where numerous metaphors transform to present the essence in a fresh light without mimicking the source language. This deliberate departure from literal translation strives for a natural and evocative rendition, providing readers with a novel perspective on the narrative. In essence, this study takes readers on a concise yet compelling journey through the art of metaphorical translation, demonstrating how linguistic choices bridge cultural gaps while preserving the emotive essence of